2008
DOI: 10.1177/153244000800800302
|View full text |Cite
|
Sign up to set email alerts
|

Party Influence on Roll Call Voting: A View from the U.S. States

Abstract: Recent studies have documented that parties influence legislative behavior. But such studies have been unable to distinguish between party voting stemming from ideological agreement and true party influence, as most lack independent measures of legislator ideology and have not been tested at the U.S. state level. Using survey data to control for legislator ideology, this analysis looks at how and under what conditions parties influence voting in three sessions of five state legislatures. The results suggest pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 33 publications
3
13
0
Order By: Relevance
“…Somewhat surprisingly, the previous literature has not taken advantage of this unique research design, neglecting the effects of electoral institutions on particularism. Several recent works take advantage of the proliferation of online voting records and sophisticated webscraping techniques have reduced the costs of collecting comprehensive state-level data (Clark et al 2009; Shor et al 2010), but those focus on the effects of legislator demographic characteristics on bill initiation and policy success (Bratton and Haynie 1999; Whitby 2002) or the role of parties in state legislatures (Battista and Richman 2011; Jenkins 2008; Wright and Schaffner 2002). Examining a sample of 165,000 bills spanning 120 years in 13 different states, Gamm and Kousser (2010) identified a considerable amount of particularistic legislation and found that particularistic legislation was related to the level of party competition in the legislature, with one party dominance associated with more particularistic bills, and members’ salaries (with higher compensation associated with more particularistic bills).…”
Section: Electoral Institutions and The Personal Votementioning
confidence: 99%
“…Somewhat surprisingly, the previous literature has not taken advantage of this unique research design, neglecting the effects of electoral institutions on particularism. Several recent works take advantage of the proliferation of online voting records and sophisticated webscraping techniques have reduced the costs of collecting comprehensive state-level data (Clark et al 2009; Shor et al 2010), but those focus on the effects of legislator demographic characteristics on bill initiation and policy success (Bratton and Haynie 1999; Whitby 2002) or the role of parties in state legislatures (Battista and Richman 2011; Jenkins 2008; Wright and Schaffner 2002). Examining a sample of 165,000 bills spanning 120 years in 13 different states, Gamm and Kousser (2010) identified a considerable amount of particularistic legislation and found that particularistic legislation was related to the level of party competition in the legislature, with one party dominance associated with more particularistic bills, and members’ salaries (with higher compensation associated with more particularistic bills).…”
Section: Electoral Institutions and The Personal Votementioning
confidence: 99%
“…Aldrich and Battista () investigate conditional party government using a sample of roll‐call votes in state legislative chambers. Jenkins (, ) has utilized survey data on state legislators to examine the factors that shape legislative decision making. Battista and Richman () utilize roll‐call data during the 1999–2000 session to uncover hidden party effects in voting behavior.…”
Section: Parties As Procedural Cartelsmentioning
confidence: 99%
“…Jenkins 2008;Battista and Richman 2011; Wright and Schaffner 2002. 53 There are many versions of the Ranney index, most of which include the party of the governor and are operationalized differently.…”
mentioning
confidence: 99%